Agglomeration and population ageing in a two region model of exogenous growth - Theresa Grafeneder-Weissteiner; Klaus Prettner (Austrian Academy of Sciences (ÖAW), Vienna Institute of Demography (VID), 2008)
This article investigates the effects of introducing demography into the New Economic Geography. We generalize the constructed capital approach, which relies on infinite individual planning horizons, by introducing mortality. The resulting overlapping generation framework with heterogeneous individuals allows us to study the effects of ageing on agglomeration processes by analytically identifying the level of trade costs that triggers catastrophic agglomeration. Interestingly, this threshold value is rather sensitive to changes in mortality. In particular, the introduction of a positive mortality rate makes the symmetric equilibrium more stable and therefore counteracts agglomeration tendencies. In sharp contrast to other New Economic Geography approaches, this implies that deeper integration is not necessarily associated with higher interregional inequality.
Keywords: 330; Agglomeration; New Economic Geography; Trade and Growth; Constructed Capital Model; Population Ageing; Alternde Bevölkerung; Agglomerationseffekt; Neue ökonomische Geographie; Theorie